PENETAPAN HARGAGABAH OLEH TENGKULAK TERHADAP PARA PETANI DI DESA SUNGAI TENGAH KECAMATAN SABAK AUH KABUPATEN SIAK DITINJAU DARI UNDANG-UNDANG NOMOR 5 TAHUN 1999 TENTANG LARANGAN PRAKTEK MONOPOLI DAN PERSAINGAN USAHA TIDAK SEHAT - Markus Van Branco Harianja; Maryati Bachtiar; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
In Indonesia, anti-monopoly law is regulated in Law Number 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition. This law is a special and comprehensive arrangement relating to competition between business actors. One of the prohibitions contained in Law Number 5 of 1999 is the prohibition on pricing. Pricing that is prohibited in the law is price fixing that comes from agreements between business actors in setting prices. In the practice of grain buying and selling, middlemen often buy rice from farmers more expensive than the reference price set by the government, causing fraud and leading to monopolistic practices. Where the standard price set by the middleman is higher than the standard price set by the National Logistics Agency. This is what causes grain production especially in the Sungai Tengah Village area to be fully controlled by middlemen in the area. In the practice of buying and selling grain by middlemen and farmers, it is very contrary to Minister of Trade Regulation No. 27 / M-DAG / Per / 5/2017. The purpose of this thesis is: First, to find out the form of monopoly and unfair business competition on grain buying and selling in Sungai Tengah Village, Sabak Auh District, Siak Regency, Second, to find out how far the price of grain by middlemen is able to increase food productivity in Siak Regency.This type of research can be classified in the type of sosiological juridical research. The research was conducted at Sungai Tengah Village, Sabak Auh District, Siak Regency. Sosiological law research uses primary data and secondary data, while population and sample are the parties related to the problem studied in this research. Technique of collecting data in this research by interview and literature study.From the results of research problems there are two main things that can be concluded. First, business actors (middlemen) in Sungai Tengah Village have violated the Republic of Indonesia Minister of Trade Regulation Number 27 / M-DAG / PER / 5/2017 concerning Reference Price for Purchasing in Farmers and Reference Sales Price at Consumers by increasing the standard of grain purchase in farmers above standard government reference price. Second, the food needs of rice farmers in Sungai Tengah Village can be fulfilled from local production in the village at harvest time, but for Siak Regency rice yields from Sungai Tengah Village cannot meet the food needs in Siak Regency considering that almost all grain production is controlled by middlemen.Key Words: Price Fixing – Grain – Monopoly – Middleman – The Farmer